2019
DOI: 10.2147/cmar.s196574
|View full text |Cite
|
Sign up to set email alerts
|

<p>T-lymphoid/myeloid mixed phenotype acute leukemia and early T-cell precursor lymphoblastic leukemia similarities with <em>NOTCH1</em> mutation as a good prognostic factor</p>

Abstract: Purpose: T-lymphoid/Myeloid Mixed phenotype acute leukemia (T/M-MPAL) is ambiguous leukemia which overlaps with early T-cell precursor lymphoblastic leukemia (ETP-ALL). We have revisited the immunophenotyping profile of T/M-MPAL and ETP-ALL to identify differences and/or similarities, as these entities represent a therapeutic challenge in clinical practice. Patients and methods: A total of 26 ETP-ALL and 10 T/M-MPAL cases were identified among 857 cases of childhood leukemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…In contrast, the ETP-ALL had a 5-year pOS of 56.7%. Recently we demonstrated that ETP-ALL with NOTCH1 mut was associated with significantly better pOS (90%) than NOTCH1 wt (pOS 37%; p = 0.017) (44). Interestingly, although the early cortical subtype had higher frequencies of NOTCH1 mut , it presented a relatively low pOS (48.6%).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the ETP-ALL had a 5-year pOS of 56.7%. Recently we demonstrated that ETP-ALL with NOTCH1 mut was associated with significantly better pOS (90%) than NOTCH1 wt (pOS 37%; p = 0.017) (44). Interestingly, although the early cortical subtype had higher frequencies of NOTCH1 mut , it presented a relatively low pOS (48.6%).…”
Section: Discussionmentioning
confidence: 99%
“…This article is protected by copyright. All rights reserved cases [17,30,37,39,40,42,43,51,[56][57][58][59][60][61]. This is in contrast to patterns of signalling alteration seen in more phenotypically mature leukaemias.…”
Section: Accepted Articlementioning
confidence: 99%
“…IL7R is responsible for the differentiation of hematopoietic cells into lymphoid progenitor cells, and its level is altered during the development of T-and B-cells [113,114]. The IL7R gene encoding the IL7R-α chain heterodimerizes with the IL7R-γ form or with the cytokine receptor-like factor 2 (CRLF2) to form IL7 receptor or thymic stromal lymphopoietin (TSLP) receptor, respectively [115][116][117].…”
Section: Interleukin-7 Receptor-α (Il7r) and Sh2b Adaptor Protein 3 (mentioning
confidence: 99%